Governance, Regulation and Management of Global Sport Organisations - Emmanuel Bayle (Routledge, 2025)
This book is a bold and ambitious analysis of the challenges facing global sport in the 21st century and how those challenges can be met through good governance, management and regulation. Connecting the political and managerial dimensions of sport, from international governing bodies such as the International Olympic Committee through to national governing bodies, leagues and professional sport organisations, the book offers a new way of thinking about the trajectory of contemporary sport. Adopting an innovative multi-level approach - across macro, meso and micro levels – the book explores the key challenges currently facing sport, including the rapid emergence of new sports such as MMA and adventure sports; the arrival of new actors in the international sport ecosystem, such as the Gulf states and private equity investment; the growth of new technologies, such as AI; and socio-political and developmental issues such as integrity, sustainability, demographic change and sport-for-development. It considers the interaction of actors at different levels, from states to athletes and across the public and private sectors, and explores different models of sport around the world, including the dominant European and North American models. Its findings support the argument that current and future international sports governance and regulation require a more complex and nuanced method of analysis. Offering a new vision for global sport, this is essential reading for advanced students, researchers, policymakers or practitioners working in sport management, governance or policy, or with a general interest in strategy, governance or public policy.
Keywords: 790; Emmanuel Bayle; sport governance; sport organisations; Olympic; sport federations; national governing bodies; NGBs; professional sport; mega-sporting events; MSEs; International Olympic Committee; IOC; volunteering; athlete voice; national Olympic committees; NOCs; European sport model; North American sport model; SPLISS model; professional leagues; professional clubs; performance management; sport management